ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN DI DISPENDA KOTA DENPASAR - Sugiantara, Pande Putu Oka; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
Nowadays, Accounting Information System technology is very rapidly growing, for example it can be used for the advancement of government agencies. Furthermore, the sustainability and success of a government agency is determined by the performance of the employees. Therefore, the aim of this study is to determine the effect of effectiveness of the accounting information system implementation, suitability of task, utilization and trust of information technology on employee performance. Sample used in this study is the employees in Local Revenue Office in Denpasar who are working in the subdivision of secretariat, data collection and assignment, billing as well as land & building tax (L&B Tax), Duty on Land and Building Right Acquisition, and income. The number of samples obtained by saturation sampling technique is 89 respondents. Furthermore, the number of questionnaires distributed was 89 questionnaires, and the questionnaires returned were 71 questionnaires. Data analysis used in this study is multiple linear regression analysis. The results of analysis show that the effectiveness of accounting information system implementation, suitability of task, utilization and trust of information technology has a positive impact to the employee performance in Local Revenue Office in Denpasar. It means that the four variables are able to improve employee performance.